2021
DOI: 10.2147/dhps.s305953
|View full text |Cite
|
Sign up to set email alerts
|

Adulterated Traditional-Herbal Medicinal Products and Its Safety Signals in Malaysia

Abstract: Background: Usage of traditional-herbal medicines (THM) for various illnesses has been increased around the world, so does the adulteration of these products with hazardous compounds. There are limited Malaysian data that have been published on the characteristics trend and adverse events associated with adulterated THM products. Aim: This study described characteristics of adulterated THM products in Malaysia and aimed to quantify THM products' safety signals of adverse reactions (ARs). Methods: THM products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Studies have shown that some THPs tend to adulterate their herbal products to sustain the claims at expense of patient safety occasioned by compromise in quality and efficacy of products. [35][36][37][38][39][40] Adulteration of herbal products can occur during production or at point of sale, and is in violation of acceptable standards and is a serious standardization problem which affects the quality and reliability of these products. 41 There is a need to employ analytical chemistry methods and DNA meta barcoding to rule out adulteration of herbal products supplied by THPs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some THPs tend to adulterate their herbal products to sustain the claims at expense of patient safety occasioned by compromise in quality and efficacy of products. [35][36][37][38][39][40] Adulteration of herbal products can occur during production or at point of sale, and is in violation of acceptable standards and is a serious standardization problem which affects the quality and reliability of these products. 41 There is a need to employ analytical chemistry methods and DNA meta barcoding to rule out adulteration of herbal products supplied by THPs.…”
Section: Discussionmentioning
confidence: 99%
“…A metasynthesis on the barrier for health-seeking behaviour among breast cancer women revealed that belief in traditional alternative care had hindered the timing of health-seeking [ 36 ]. Secondly, the hepatotoxicity of the substances or contaminants may promote HCC development, especially among the unregistered traditional products with unknown safety profiles [ 37 , 38 ]. Therefore, strict regulation on traditional medication marketing and usage is critical for avoiding patient harm.…”
Section: Discussionmentioning
confidence: 99%
“…Another form of adulteration involves substituting a cheaper or more readily available herb for another, even if it has a less favorable safety profile. [39][40][41][42] Among the most common adulterants are pharmaceuticals intended to alleviate discomforting symptoms, including nonsteroidal anti-inflammatory drugs and antihistamines. Adulteration is a pervasive issue in the realm of steroids and sexual-enhancing drugs, with Sildenafil being a commonly reported culprit.…”
Section: Anticipating Adverse Effects and Toxicities: Understanding H...mentioning
confidence: 99%